2017
DOI: 10.1371/journal.pone.0182543
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of preoperative anemia, abnormal mean corpuscular volume and red cell distribution width among surgical patients in Singapore, and their influence on one year mortality

Abstract: IntroductionPreoperative anemia and high red cell distribution width (RDW) are associated with higher perioperative mortality. Conditions with high RDW levels can be categorized by mean corpuscular volume (MCV). The relationship between RDW, anemia and MCV may explain causality between high RDW levels and outcomes. We aim to establish the prevalence of preoperative anemia and distribution of RDW and MCV among pre-surgical patients in Singapore. In addition, we aim to investigate the association between preoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 50 publications
4
49
0
1
Order By: Relevance
“…Sex differences in the prevalence of anemia across different age groups were also found, with the prevalence being higher in females than in males aged <70 years, which reversed in those aged ≥70 years. This trend among those aged ≥70 years has also been demonstrated in other studies, 8,16 in which age was associated with both Hb and anemia and with a stronger effect in males than in females and an even higher prevalence of anemia in males aged 71-74 years.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Sex differences in the prevalence of anemia across different age groups were also found, with the prevalence being higher in females than in males aged <70 years, which reversed in those aged ≥70 years. This trend among those aged ≥70 years has also been demonstrated in other studies, 8,16 in which age was associated with both Hb and anemia and with a stronger effect in males than in females and an even higher prevalence of anemia in males aged 71-74 years.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies of the prevalence of anemia have been reported, but large‐scale general population‐based study are rare. Moreover, there are regional variations in anemia prevalence due to differences in race, diet, endemic diseases, and epigenetic influences .…”
Section: Introductionmentioning
confidence: 99%
“…In children, anemia is associated with reduced quality of life and cognitive abnormalities [3,4]. Anemia is also associated with increased post-operative mortality in adults and overall mortality in older adults [5,6]. Atopic diseases such as atopic dermatitis, allergic rhinitis, and asthma also have a high and increasing prevalence in the general population [7,8], and they have been associated with other medical conditions, such as rheumatoid arthritis, inflammatory bowel disease, and anxiety or depression [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Based on analytical principles mentioned above, univariate and multiple linear regression models were used to assess relationships with preop-eGFR and postoperative thirty-day mortality. Three models(an unadjusted model, a demographically adjusted model, and a fully-adjusted model) were constructed according to the STROBE statement [24].As for the fully-adjusted model, those adjusted variables, reported in previous studies, are related covariates that may affect preop-eGFR and/or thirty-day mortality [22] [20].Moreover, subgroup analyses were performed by stratified linear regression models. Subgroup interaction test was performed to verity the effect modification by subgroup and then a likelihood ratio test was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Variables of the database file included: demographic information; preoperative comorbidities;preoperative laboratory perioperative blood transfusion data; anesthesia type ;priority of surgery ; surgical risk classification( based on the 2014 ESC/ESA guidelines on non-cardiac surgery [18] [19]);and postoperative thirty-day prognosis. Preoperative comorbidities were consist of anemia,CKD, and medical history [cerebrovascular accidents (CVA), ischemic heart disease (IHD), congestive heart failure (CHF),type1 diabetes].Those medical histories mentioned above were also associated with Revised Cardiac Risk Index (RCRI) score [17].The latest results of preoperative laboratory test were mainly about eGFR, red blood cell distribution width (RDW)(Levels above 15.7% were defined as high RDW ,as the normal reference range was 10.9-15.7% [22]), hemoglobin.We listed in detail the covariates used in this study. In short, their reasons for inclusion included as follows: (1) demographic data; (2) variables that can affect preop-eGFR or thirty-day mortality reported by previous literature [20]; (4) based on our clinical experiences.…”
Section: Measurement Of Preop-egfr Thirty-day Mortality and Other Comentioning
confidence: 99%